2021
DOI: 10.1108/jaar-07-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ownership structure, board attributes and XBRL mandate on timeliness of financial reporting: evidence from Turkey

Abstract: PurposeThe purpose of this study is to investigate the effects of ownership structure, board attributes and eXtensible Business Reporting Language (XBRL) on annual financial reporting timeliness of non-financial companies listed on Borsa Istanbul (BIST).Design/methodology/approachTo conduct the analyses, the authors used two samples. The main sample consists of 187 companies, while the subsample includes 54 companies in the BIST 100 index. The data set covers the 2010–2018 period. To investigate the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 66 publications
(95 reference statements)
3
26
0
Order By: Relevance
“…In the Turkish markets, Aksoy et al (2021) explored the impact of ownership structure and board composition on the annual financial reporting timeliness of non-financial companies listed on Borsa Istanbul. The results indicated that companies with a high level of institutional ownership and women board membership file annual reports earlier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Turkish markets, Aksoy et al (2021) explored the impact of ownership structure and board composition on the annual financial reporting timeliness of non-financial companies listed on Borsa Istanbul. The results indicated that companies with a high level of institutional ownership and women board membership file annual reports earlier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DXBRL is a dummy variable (see e.g. Aksoy et al. , 2021) that equals one for post-XBRL adoption (the period of 2015–2019) and zero for otherwise (the period of 2010–2014).…”
Section: Methodsmentioning
confidence: 99%
“…A core block of contributions focuses on what RegTech is, essentially the merging of regulation and technology. RegTech solutions drive digitalisation and digital innovation, affecting vast swaths of organisations, entities and authorities, providing the means to improve areas such as digital reporting, and potentially upturning preexisting structures and re-shaping regulatory processes and systems (Aksoy et al, 2021;Arner et al, 2020;Kavassalis et al, 2018;Kurum, 2020). These automated, digital and non-invasive solutions (Chiu & Deipenbrock, 2021;FCA, 2016;Quill & Lennon, 2019) provide users with a seamless experience, can be adapted dynamically and expediently, and enable real-time operations, yet remain scalable (Kavassalis et al, 2018;Laguna de Paz, 2022;Michaels & Homer, 2018;Quill & Lennon, 2019;Sangwan et al, 2019).…”
Section: Dimension #1: Regulation and Technologymentioning
confidence: 99%